Analisis Manajemen Diri Lansia Yang Menderita Hipertensi di Panti Sosial Tresna Werdha PSTW Kasih Sayang Ibu Batusangkar Tahun 2022 - Oktarida, Rosi; Putri, Lydia Mardison; Lazdia, Wenny (Universitas Fort De Kock Bukittinggi, 2023)
Background: The incidence of hypertension will continue to increase as a person's age increases and reaches a peak at the age of over 65 years with a figure of 65%. The purpose of the study was to determine the self-management of hypertension in the elderly at Pstw Kasih Sayang Ibu in Batusangkar. Methods: This research is quantitative with descriptive research design. The population in this study were all the elderly at PSTW Kasih Sayang Ibu Batu Sangkar with hypertension as many as 60 people. The research was conducted in January-June 2022 . The sample of this study were 60 elderly people. Sampling with total sampling, data were analyzed univariately. Results: The results of the univariate analysis showed that most of the elderly had good hypertension management (73.3 %), hypertension treatment was good (75%), did not do good hypertension prevention (56.7%) and experienced development and complications. good hypertension (78.3%). Conclusion: So, the problem is that most of the elderly do prevention of hypertension which is not good , namely as many as 34 (56.7%) elderly. It is expected for the elderly to make efforts to prevent hypertension even better. The elderly are also required to reduce salt consumption and the use of salt in food, reduce caffeine consumption and reduce the frequency of smoking.